How Do Ecommerce App Users Continue To Use The Platforms? - Astra Prima Budiarti (Jurnal Manajemen Universitas Bung Hatta, 2023)
This study investigates the effects of cognitive absorption and perceived usefulness on the users intention of online shopping platforms to continue using those platforms, both direct and indirect. Indirect influence is mediated by trust. In this study, complicated structural models can be tested using structural equation modeling (SEM) analysis. According to this study, cognitive absorbtion, perceived usefulness, and trust all influence continuation intention. The study's target audience is made up of users of e-commerce platforms. The accidental sampling technique was used to randomly sample 253 respondents in total. However, the indirect relationship between cognitive absorption and continuance intention is not considerably impacted by trust. This is impacted by individuals' tendencies to disregard trust when they are highly engaged with the sites they utilize.